Visual Narratives on TikTok: Analysis of the Impact on Engagement Based on the Tone of Scientific News Published by Media in Spain and Chile - Martin-Neira, Juan-Ignacia; Irarrázaval, José; Gómez, Rocío (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study focuses on analysing how four television media in Spain and Chile have adopted TikTok as a tool to disseminate scientific content. Through an analysis of the publications made in 2023, the visual narratives used are explored, classifying the publications according to their tone and style, and thus relating public interaction to the type of message. The results obtained preliminarily suggest that tone influences engagement rates with users; however, other elements such as format or the context of the information cannot be overlooked.